The differences and similarities between curiosity and interest: Meta-analysis and network analyses. (August 2022) - Tang, Xin; Renninger, K. Ann; Hidi, Suzanne E.; Murayama, Kou; Lavonen, Jari; Salmela-Aro, Katariina
Abstract: Three studies on the relationship between curiosity and interest are reported. The first study was a meta-analysis that examined the Pearson correlations between scales assessing curiosity and interest. Based on 24 studies (31 effect sizes), we found that the curiosity scales correlated with the interest scales at a moderate level ( r  = 0.53), but they had extremely high heterogeneity. The second and third studies applied network analyses (i.e., co-occurrence analysis and correlation-based analysis) to data that was collected using experience sampling method. Across the studies, we found that while the feelings of curiosity reflected feelings of inquisitiveness, the feelings of interest were aligned with positive affect such as enjoyment and happiness. Importantly, an asymmetrical pattern also was found in curiosity-interest co-occurrences: when feelings of curiosity occurred, the co-occurrence of feelings of interest was highly likely, but not so vice versa. Overall, our findings suggest that feelings of curiosity are special cases of feelings of interest that pertain to knowledge acquisition. Theoretical and practical implications of these findings are discussed. Highlights: Our meta-analysis showed that curiosity correlated moderately with the interest. Meta-analysis also showed that the correlation is highly heterogeneous. Experience data of curiosity and interest were analyzed using network analyses. Feelings of curiosity reflected feelings of inquisitiveness and eagerness to know. The presence of curiosity accompanies with interest high likely, but not vice versa.